Pasang surut air laut disebabkan oleh udara yang tertutup / Abd Rachem, Novaria Angriani, Ardiyansah Yuliniar Firdaus - ABD RACHEM, 1963-; Novaria Angriani; Ardiyansah Yuliniar Firdaus (Leutikaprio, 2014)
vi, 59 hlm. : ilus. ; 19 cm